A scoping review of physical activity interventions for older adults - Taylor, Jennifer (Int J Behav Nutr Phys Act, 2021)
BACKGROUND: To inform implementation and future research, this scoping review investigates the volume of evidence for physical activity interventions among adults aged 60+. Our research questions are: (1) what is the evidence regarding interventions designed to increase total physical activity in adults aged 60+ years, in accordance with three of the four strategic objectives of GAPPA (active societies, active environments, active people); (2) what is the current evidence regarding the effectiveness of physical activity programmes and services designed for older adults?; and (3) What are the evidence gaps requiring further research? METHODS: We searched PEDro, MEDLINE, CINAHL and Cochrane from 1 January 2010 to 1 November 2020 for systematic reviews and meta-analyses of physical activity interventions in adults aged 60+. We identified interventions designed to: (1) increase physical activity; and (2) deliver physical activity programmes and services in home, community or outpatient settings. We extracted and coded data from eligible reviews according to our proposed framework informed by TIDieR, Prevention of Falls Network Europe (PROFANE), and WHO’s International Classification of Functioning, Disability and Health (ICF). We classified the overall findings as positive, negative or inconclusive. RESULTS: We identified 39 reviews of interventions to increase physical activity and 342 reviews of programmes/services for older adults. Interventions were predominantly structured exercise programmes, including balance strength/resistance training, and physical recreation, such as yoga and tai chi. There were few reviews of health promotion/coaching and health professional education/referral, and none of sport, workplace, sociocultural or environmental interventions. Fewer reported outcomes of total physical activity, social participation and quality of life/well-being. We noted insufficient coverage in diverse and disadvantaged samples and low-middle income countries. CONCLUSIONS: There is a modest but growing volume of evidence regarding interventions designed to increase total physical activity in older adults, although more interventional studies with long term follow-up are needed, particularly for GAPPA 1. Active Societies and GAPPA 2. Active Environments. By comparison, there is abundant evidence for GAPPA 3. specific programmes and services, but coverage of sport and workplace interventions, and diverse samples and settings is lacking. Comprehensive reviews of individual studies are now needed as well as research targeting neglected outcomes, populations and settings.